Elucidation of mRNA targets of miR-145-5p in diabetic kidney disease using bioinformatics analysis - Zahari Sham, Siti Yazmin; Azwar, Shamin; Wai, Kien Yip; Abdullah, Maha; Thevandran, Kalaiselvam; Osman, Malina; Heng, Fong Seow (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2022)
Introduction: Diabetic kidney disease (DKD) is a major global cause of end-stage-kidney disease. In view of its on- going risk of disease progression, the search for a better biomarkers and treatment led to the discovery of microRNAs which regulate gene expression post-translationally. Recently, we reported a trend of upregulation of miR-145-5p in sera of type 2 diabetic patients with macroalbuminuria in a selected Malaysian population, which concurred with previous in vivo and in vitro studies of DKD. In addition, miR-145 has been implicated as a tumour suppressor in various cancers. Methods: In this study, bioinformatics tools were utilized to predict the mRNA targets of miR- 145-5p. Results: A total of 683 and 224 experimentally-validated mRNA targets of miR-145-5p were identified by Tarbase and miRTarbase, respectively. Eighty-six (86) commonly identified targets were submitted to Metascape and Enrichr for enrichment analysis. Bioinformatics analysis and literature search suggested that insulin receptor substrate 1 (IRS1) was the most promising target of miR-145-5p. Its associated Gene Ontology terms and pathways included insulin-like growth factor receptor signalling and Forkhead transcription factors (FOXO), respectively. Based on these analyses, the roles of IRS1 in DKD were proposed. Conclusion: As the kidneys are heterogenous in cell types and the mechanism of miRNA is cell-type-dependent, target prediction of miR-145-5p by bioinformatics analysis is particularly important in DKD, to improve the likelihood of a successful in vitro experimental verification in specific renal cell types. In addition, this study attempts to utilize bioinformatics studies, which is not widely done in DKD, as recently reported.